Does working memory improvement benefit from sleep in older adults? - Negin Sattari; Lauren N. Whitehurst; Maryam Ahmadi; Sara C. Mednick (Neurobiology of Sleep and Circadian Rhythms, 2019)
Working Memory (WM), is an important factor influencing many higher-order cognitive functions that decline with age. Repetitive training appears to increase WM, yet the mechanisms underlying this improvement are not understood. Sleep has been shown to benefit long-term memory formation and may also play a role in WM enhancement in young adults. However, considering age-related decline in sleep, it is uninvestigated whether sleep will facilitate WM in older adults. In the present work, we investigated the impact of a nap, quiet wakefulness (QW) and active wakefulness (AW) on within-day training on the Operation Span (OSPAN) task in older adults. Improvement in WM was found following a nap and QW, but not active wake. Furthermore, better WM was associated with shared electrophysiological features, including slow oscillation (SO, 0.5–1 Hz) power in both the nap and QW, and greater coupling between SO and sigma (12–15 Hz) in the nap. In summary, our data suggest that WM improvement in older adults occurs opportunistically during offline periods that afford enhancement in slow oscillation power, and that further benefits may come with cross-frequency coupling of neural oscillations during sleep. Keywords: Executive function, Sigma/SO coupling, Napping, Slow oscillation, Quiet wake, Active wake